2011
DOI: 10.1016/j.aquaculture.2011.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of human chorionic gonadotropin (hCG) and gonadotropin-releasing hormone agonist (GnRHa) treatments on the stimulation of male Senegalese sole (Solea senegalensis) reproduction

Abstract: The aquaculture of Senegalese sole (Solea senegalensis) is limited by the failure of cultured breeders (G1 generation) to produce fertilized spawning. Critical reproductive dysfunctions have been observed in both female and male Senegalese sole cultured breeders, including reduced fecundity and diminished sperm production. The present work aimed to study the effectiveness of different hormonal treatments on the stimulation of male reproduction. Male Senegalese sole cultured breeders were treated with 1) saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 45 publications
2
23
1
3
Order By: Relevance
“…; Guzmán et al . ). Combined treatment of GnRHa with 11‐ketoandrostenedione, an 11KT precursor (Agulleiro et al .…”
Section: Broodstock Managementmentioning
confidence: 97%
“…; Guzmán et al . ). Combined treatment of GnRHa with 11‐ketoandrostenedione, an 11KT precursor (Agulleiro et al .…”
Section: Broodstock Managementmentioning
confidence: 97%
“…Moreover, there was a couple which spawned formed of only cultured breeders in 2014 and the same cultured female spawned with one wild male, which had reproduced with another wild female. This is not the first report of cultured Senegalese sole participating in the spawning season, Guzmán et al (2011) observed 1 fertilised spawn of a total of 60 spawns after GnRHa implants applied into the females and hCG treatment in males, however, the two spawns obtained in the present study were naturally achieved. Furthermore, found a fidelity of mating couples over years, which this situation has been also observed in our study showing the importance of the mate choice in this species.…”
Section: Discussioncontrasting
confidence: 50%
“…For example, and applied Gonadotropin-Releasing Hormone analogue (GnRHa) implants and injections in cultured Senegalese sole obtaining spontaneous spawning but the eggs were not fertilized. The same researchers Guzmán et al, 2011) also applied human Chorionic Gonadotropin (hCG) and different doses of GnRHa in cultured males obtaining significantly more production of sperm, however, the spawned eggs were still mainly unfertilized with just one spawn obtained from cultured animals after applying double GnRHa treatment in cultured females and hCG in cultured males (Guzmán et al, 2011). These results suggested that hormonal issues in the control of gametogenesis were not the reason of the reproductive dysfunction in cultured breeders .…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations